1980
DOI: 10.1139/p80-149
|View full text |Cite
|
Sign up to set email alerts
|

Line identifications and lifetime measurements in singly and doubly excited C IV and in C V

Abstract: Forty-eight new uv lines have been observed and identified in the singly and doubly excited systems of C IV, and in C V. The beam-foil technique was used to excite the spectra and to measure radiative lifetimes for 16 levels. Good agreement is found with available theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Thus it is noteworthy that six of the tentative identifications made by Berry et al have been shown to be valid. More measurements were performed by To et al [54] and Jacques et al [143]. Here wavelengths up to 2500A were included.…”
Section: B2+mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is noteworthy that six of the tentative identifications made by Berry et al have been shown to be valid. More measurements were performed by To et al [54] and Jacques et al [143]. Here wavelengths up to 2500A were included.…”
Section: B2+mentioning
confidence: 99%
“…measured by Jacques et al [143]. In an experimental work of Blanke et al [148] also the lifetimes of ls2p3d 4P0, 4D0 were measured and from a cascade analysis the lifetime of the [144] a detailed experimental study was combined with extensive accurate calculations by Chung.…”
Section: B2+mentioning
confidence: 99%
“…The prerequisite for the validity of this approximation, an electronic transition outside a frozen core is fulfilled for the ls2s3d 4D levels but certainly not for the transitions involving the ls2p core. The results of this approximation are given in Tables I, 11.…”
mentioning
confidence: 99%
“…For the system of Li-like C , the transition probabilities of the 1s 2 2p 2 P o 1/2,3/2 → 1s 2 2s 2 S 1/2 transitions were measured by Berkner et al (1965) using the foil-excitation technique and by Knystautas et al (1971) using the beam-foil technique, respectively. There are also a number of measurements of lifetimes in C using the beam-foil technique (Donnelly et al 1978;Buchet-Poulizac & Buchet 1973b;Jacques et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The transition rates of the 2p 2 P o 1/2,3/2 → 2s 2 S 1/2 transitions were measured by Knystautas et al (1971) using the beam-foil technique. By using the same technique, the lifetimes for a number of excited states were measured in four different experimental works (Donnelly et al 1978;Buchet-Poulizac & Buchet 1973b;Jacques et al 1980;Peach et al 1988). In Table A6, we compare the theoretical results, from present calculations and MCHF-BP calculations, with the NIST recommended values and observed values.…”
mentioning
confidence: 99%